Electrolyte Solvation and Ionic Association: VIII. Reassessing Raman Spectroscopic Studies of Ion Coordination for LiTFS. Issue 6 (1st June 2022) - Henderson, Wesley A.; Helm, Monte L.; Seo, Daniel M.; Trulove, Paul C.; De Long, Hugh C.; Borodin, Oleg
Abstract : Raman spectroscopy is widely used to evaluate the ionic interactions and solvates present in electrolytes. As shown here, however, Raman spectra for crystalline solvates containing the lithium bis(trifluoromethanesulfonyl)imide (or amide) (i.e., LiN(SO2 CF3 )2, LiTFSI, LiTFSA, LiNTf2 or LiTf2 N) salt indicate that the commonly used vibrational band analyses are likely to be inaccurate and thus result in misleading conclusions about the ion interactions in liquid electrolytes with this salt. In particular, it is found by examining the Raman spectrum of a known crystalline solvate with the CIP-I- C 2 coordination mode (i.e., a TFSI − anion with a C 2 conformation coordinated to a single Li + cation via a single oxygen atom), that the vibrational band for this mode of coordination overlaps (or is closely positioned beside) that for the uncoordinated (i.e., SSIP) TFSI − anion. This realization further complicates the assessment of Raman data for LiTFSI-based electrolytes.